Immunohistochemical Subtype and Parameters of International Prognostic Index in the New Prognostic Model of Diffuse Large B-Cell Lymphoma - SV Samarina; AS Luchinin; NV Minaeva; IV Paramonov; DA D’yakonov; EV Vaneeva; VA Rosin; VA Rosin (Клиническая онкогематология)

(untitled)
Aim. To develop an integrated prognostic model of diffuse large B-cell lymphoma (DLBCL) on the basis of immunohistochemical tumor subtype and parameters of International Prognostic Index (IPI).